PEMBERONTAKAN RUH DALAM CERPEN AL-DUNYA AL-RIWAYAH (DUNIA PANGGUNG SANDIWARA) KARYA TAUFIQ EL-HAKIM - Ahmad Sahal Mubarok (BARA AJI: Jurnal Keilmuan Bahasa Arab dan Pengajarannya, 2023)
Short stories as a work of art serve as a glimpse of the record of life, or also as documentation. The dialectical relationship between short stories and reality proves that short stories can be analyzed from various angles, such as philosophy, religion, sociology, culture and stylistics. Through the stylistic approach, the author examines several phenomena mentioned in the short story al-Dunya al-Riwayah (world of theatrical stage) by Taufiq el-Hakim especially those related to human life events. The dialectical relationship between short stories and reality proves that short stories can also be analyzed from various angles, such as philosophy, religion, sociology, culture and stylistics. The strength of this influence is supported by the ability of the text to regulate coherent and contradictory relations between units of discourse units and the selection of contextual references that allow readers to interpret them. Keywords: Short Story, Realism, Stylistics.